Plant Genetics and Biotechnology in Biodiversity - Rosa Rao (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Plant genetic resources for food and agriculture (PGRFA) have been collected and exchanged for centuries. The rapid development of novel tools for genetic and phenotypic analysis is changing the way we can uncover diversity and exploit its value in modern agriculture. The integration of novel analytical tools is crucial for translating research into much-needed, more efficient management and use of PGRFA. This Special Issue provides an overview of recent topics on plant genetics and biotechnology in biodiversity. The proposed reviews and research papers present current trends and examples of genetic resources' description, conservation, management, and exploitation, highlighting that new approaches and methodogies can increase our understanding and efficient use of PGRFA to address the agricultural challenges that lie ahead.